External Validation of a Prognostic Model for Survival of Patients With Abdominal Aortic Aneurysms Treated by Endovascular Aneurysm Repair - Dabravolskaité, Vaiva (Elsevier, 2025)
Objective
Current guidelines recommend diameter monitoring of small and asymptomatic abdominal aortic aneurysms (AAAs) due to the low risk of rupture. Elective AAA repair is recommended for diameters ≥ 5.5 cm in men and ≥ 5.0 cm in women. However, data supporting the efficacy of elective treatment for all patients above these thresholds are diverging. For a subgroup of patients, life expectancy might be very short, and elective AAA repair at the current threshold may not be justified. This study aimed to externally validate a predictive model for survival of patients with an asymptomatic AAA treated by endovascular aneurysm repair (EVAR).
Methods
This was a multicentre international retrospective observational cohort study. Data were collected from four European aortic centres treating patients between 2001 and 2021. The initial model included age, estimated glomerular filtration rate (eGFR), and chronic obstructive pulmonary disease (COPD) as independent predictors for survival. Model performance was measured by discrimination and calibration.
Results
The validation cohort included 1 500 patients with a median follow up of 65 months, during which 54.6% of the patients died. The external validation showed slightly decreased discrimination ability and signs of overfitting in model calibration. However, a high risk subgroup of patients with impaired survival rates was identified: octogenarians with eGFR < 60 OR COPD, septuagenarians with eGFR < 30, and septuagenarians with eGFR < 60 and COPD having survival rates of only 55.2% and 15.5% at five and 10 years, respectively.
Conclusion
EVAR is a valuable treatment option for AAA, especially for patients unsuitable for open repair. Nonetheless, not all these patients will benefit from EVAR, and an individualised treatment recommendation should include considerations on life expectancy. This study provides a risk stratification to identify patients who may not benefit from EVAR using the present diameter thresholds.